Anti-predatory responses of the thick shell mussel Mytilus coruscus exposed to seawater acidification and hypoxia. (August 2015) - Sui, Yanming; Hu, Menghong; Huang, Xizhi; Wang, Youji; Lu, Weiqun
Abstract: Ocean acidification and hypoxia, both caused by anthropogenic activities, have showed deleterious impacts on marine animals. However, their combined effect on the mussel's defence to its predator has been poorly understood, which hinders us to understand the prey–predator interaction in marine environment. The thick shell mussel Mytilus coruscus and its predator, the Asian paddle crab Charybdis japonica were exposed to three pH levels (7.3, 7.7, 8.1) at two concentrations of dissolved oxygen (2.0 mg L −1, 6.0 mg L −1 ) seawater. The anti-predatory responses of mussels, in terms of byssus thread production were analyzed after 72 h exposure. During the experiment, frequency of shedding stalks (mussels shed their byssal stalks to release themselves from attachment and allow locomotion) and number of byssus threads increased with time, were significantly reduced by hypoxia and low pH levels, and some interactions among time, predator, DO and pH were observed. As expected, the presence of the crab induced an anti-predator response in M. coruscus (significant increases in most tested parameters except the byssus thread length). Acidification and hypoxia significantly reduced byssus thread diamter at the end of the experiment, but not the byssus thread length. Cumulative byssus thread length and volume were significantly impaired by hypoxia and acidification. Our results highlight the significance of anti-predatory responses for adult mussel M. coruscus even under a stressful environment in which stress occurs through ocean acidification and hypoxia. By decreasing the strength of byssus attachment, the chance of being dislodged and consumed by crabs is likely increased. Our data suggest that there are changes in byssus production induced by hypoxia and acidification, which may affect predation rates on M. coruscus in the field. Highlights: Combined effects of hypoxia and acidification on the anti-predatory traits are investigated. Crab induces anti-predatory responses in mussels. Hypoxia and acidification impair the anti-predatory responses of mussels. Hypoxia and acidification may change the prey–predator dynamics.